2007
DOI: 10.1074/jbc.m704330200
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of G Signaling 16 Is a Marker for the Distinct Endoplasmic Reticulum Stress State Associated with Aggregated Mutant α1-Antitrypsin Z in the Classical Form of α1-Antitrypsin Deficiency

Abstract: In the classical form of ␣ 1 -antitrypsin deficiency, a mutant protein accumulates in a polymerized form in the endoplasmic reticulum (ER) of liver cells causing liver damage and carcinogenesis by a gain-of-toxic function mechanism. Recent studies have indicated that the accumulation of mutant ␣ 1 -antitrypsin Z in the ER specifically activates the autophagic response but not the unfolded protein response and that autophagy plays a critical role in disposal of insoluble ␣ 1 -antitrypsin Z. In this study, we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 35 publications
0
75
1
1
Order By: Relevance
“…However, recently we discovered by genomic analysis a marked upregulation of regulator of G signaling 16 (RGS16) and a smaller increase in RGS5 in the liver of the Z mouse, a mouse that has hepatocyte-specific inducible expression of ATZ. 34 These results were highly statistically significant because they were compared with expression of the same gene products in the liver of the Z mouse in the uninduced state, in the liver of control mice with hepatocyte-specific inducible expression of the wild-type human AT gene and in the liver of nontransgenic littermates of the same original genetic background. The increase in RGS16 expression was quite marked in magnitude and was apparent at any time during the day, eliminating the possibility that it was because of a peculiar diurnal effect or a difference in feeding associated with the AT deficiency state.…”
Section: Potential Mechanisms For Activation Of Hepatic Autophagy In mentioning
confidence: 99%
“…However, recently we discovered by genomic analysis a marked upregulation of regulator of G signaling 16 (RGS16) and a smaller increase in RGS5 in the liver of the Z mouse, a mouse that has hepatocyte-specific inducible expression of ATZ. 34 These results were highly statistically significant because they were compared with expression of the same gene products in the liver of the Z mouse in the uninduced state, in the liver of control mice with hepatocyte-specific inducible expression of the wild-type human AT gene and in the liver of nontransgenic littermates of the same original genetic background. The increase in RGS16 expression was quite marked in magnitude and was apparent at any time during the day, eliminating the possibility that it was because of a peculiar diurnal effect or a difference in feeding associated with the AT deficiency state.…”
Section: Potential Mechanisms For Activation Of Hepatic Autophagy In mentioning
confidence: 99%
“…Misfolded proteins within the ER lumen usually trigger adaptive measures termed the unfolded protein response (UPR). Indeed, terminally misfolded truncated variants of α 1 -antitrypsin (e.g., α 1 -antitrypsin NullHongKong and Saar) constitutively activate the UPR [32,33]. Surprisingly, the accumulation of Z α 1 -antitrypsin polymers within the ER is not associated with UPR activation in cell lines that recapitulate hepatocyte phenotypes or in transgenic mice, possibly because polymers are structurally ordered (Fig.…”
Section: Intracellular Processing Of α α α α 1 -Antitrypsin Polymersmentioning
confidence: 99%
“…Instead Z α 1 -antitrypsin expression activates NFκB by a calcium-mediated pathway that is independent of the UPR [32][33][34][35]. We have termed this the 'ordered protein response' [35] and others have shown that it results in the release of IL-6 and IL-8 [34].…”
Section: Intracellular Processing Of α α α α 1 -Antitrypsin Polymersmentioning
confidence: 99%
“…In mammalian cells, the AT-Z-induced response to aggregates may be mediated in part by the regulator of G signaling 16 protein. Regulator of G signaling 16 protein is an inhibitor of an autophagy-repressing G protein, Gai3, and is specifically induced by AT-Z in cell and mouse models, and in the livers of patients with ATD (42).…”
Section: Autophagy and The Destruction Of The Z Variant Of Antitrypsinmentioning
confidence: 99%